KEBIJAKAN OPERASIONAL DAN KEPUTUSAN PENDANAAN PADA PERUSAHAAN DAERAH AIR MMINUM KOTA MALANG - INDRA JUWONO (Jurnal Akademika, 2015)
The funding decision is basically concerned with the selection of the source of funds by thecompany. There are a number of risks that affect the company's performance to beconsidered by the parties, namely the risk of macro-economic and micro-economic risks. Thisstudy aims to determine and prove the influence of operational policy and funding decisionson the financial performance of local water company in the city of Malang.Based on the theory and the results of previous research, this study uses the variableoperational decisions comparison between the results of Sales by Total Assets, andcomparisons between the results of the sales receivables. While the funding decisions usingindicators and debt ratio Debt to Equity Ratio (DER). Furthermore, the company'sfinancial performance variables using ROI and ROE indicators. The analysis in this studyuses multiple regression analysis to determine the independent variables and the dependentvariable population in this study is the monthly financial reports by local water companiesMalang starting in 2008 until the year 2010 that collected 36 observations.Based on the analysis of the results of research and discussion, we can conclude that the threehypotheses stated previously proved significant. From this analysis it can be concluded thatthe operational policies and funding decisions affect the financial performance of local watercompany MalangKeywords: operational policy, funding decisions, financial performance